The Mediatory Role of Supply Chain Collaboration between Human Resource Management Practices and Port Performance - Saud Mira, Mohammed; Voon Choong , Yap; Binti Alias, Mazni (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of the study is to investigate the mediating role of supply chain collaboration (SCC) between human resource management practices (HRMP) and port performance (PP) in Kingdom of Saudi Arabia (KSA) ports based on the assumption of Maslow’s hierarchy of needs and Adams’ equity theories. The 221 data has been collected from different firms that are engaged with KSA ports logistics. The data has been investigated to apply smartPLS-3. The study found the full mediation role of SCC between HRMP and PP. Furthermore, the study revealed the positive and significant relationship between HRMP and SCC. However, the SCC is very important for effective implementation of HRMP and as well as for positive performance of posts in KSA. Future studies should validate the current study framework in other contexts, specifically in developing countries, to validate the study.